Mormonism as the Form of Exceptionalism in American Frontier - Nopita Trihastutie (Universitas Brawijaya, 2018)
Frontier is a movement beyond the patronage of cultural life expression occurred in the Western America during the colonial period to the early twentieth century. The frontier periods evolved romance and vio-lence that resulted in an exceptionalism, a special term in the life of religious denomination in America. It was particularly when visions of paradise overwhelmed the 19th century America in the time of the emer-gence of Mormonism. This study focuses on how Mormonism represents the exceptionalism in the fron-tier experience. This study corresponds to one of Wilhelm Dilthey’s hermeneutics that emphasizes on the interpretation as the primary method to validate one’s sense of historical moments and cultural contexts. The findings reveal two major things: first, Mormon peoples and their religious practices in the Old West can be considered as a distinctive religious revival to the historical model of the frontier. Second, Mor-monism cannot be generalized as Christianity or as one of the Christian denominations. Instead, Mormon religious philosophy and practices mark the existence of exceptionalism in the frontier experience.